The Relationship Between the State and Muslim Civil Society in Zakat Management in Indonesia - Emzaed, Ali Murtadho; Sadiani, Sadiani; Munib, Munib (Transformatif, 2023)
This article aims to discuss the relationship between the state and Muslim civil society in managing zakat in Indonesia. The practice of zakat management in Indonesia has experienced ups and downs in the context of relations between the state and Muslim civil society. However, this kind of relationship does not hinder efforts to manage zakat optimally. Zakat management through zakat institutions has great benefits when compared to non-institutionalized zakat management. This article attempts to answer the question of what is the relationship between the state and Muslim civil society in managing zakat in Indonesia? Why is institutionalizing zakat important in efforts to manage zakat in Indonesia? This article is a type of literature research with a ma'na cum maghza approach which has found, first, that the management of zakat is in the domain of Muslim civil society in its relations with the state, especially after Indonesia's independence. The relationship between the National Amil Zakat Agency (BAZNAS) which is affiliated with the state and the National Amil Zakat Institute (LAZNAS) which is affiliated with Muslim civil society is synergistic in efforts to manage zakat optimally. However, after the enactment of Law Number 23 of 2011 concerning Zakat Management, the state attempted to manage zakat nationally through the existence of BAZNAS. Secondly, zakat management in a zakat institution is important in an effort to optimize professional zakat management as indicated in Surah at-Taubah verse 60 which is represented through the existence of BAZNAS and LAZNAS